Educating Adults in Uganda : Findings and Signals - Oxenham, John (2012)
The note summarizes a 1999 evaluation of adult literacy programs in Uganda, which looked at the longer-term outcomes of these programs. Four main questions were addressed: How well do adult literacy students remember how to read, write, and calculate? To what extent do they use their skills? Compared with non-literates, what knowledge of "functional" topics do they exhibit, and to what extent do they practice what was learnt? Which are the most effective approaches to literacy teaching, and what are the comparative costs? Some questions were left open, such as the treatment of literacy instructors, which engenders uncertainty towards policy formation, and, the balance to be sought between general, national curriculum, and an array of curricula tailored to suit different interest groups. Evident signals seemed to confirm the importance of reliable delivery of sound instruction, rather than methods, and materials, and, as for policy, the strong signal is that frameworks to encourage active, complementary partnerships between governments, and agencies, would best serve the people who could benefit from adult basic education. Thus, there is an impending need to develop ways of combining basic education in a vernacular introduction, to an official language.